Enhancing Soil Fertility Status, Sweet Potato Yield and Tuber Nutrient Composition through Different Manure Sources in Southeastern Nigeria - , J. C. Nwite (Archives of Current Research International, 2016)
The experiment was carried out to investigate the effects of different manure sources on selected soil chemical properties, sweet potato tuber yield and tuber nutrient compositions. The high yielding sweet potato varieties are fertilizer responsive. Research evidences indicated that the application of inorganic fertilizers increases root yield, but hampers the quality of sweet potato. Inorganic fertilizers are believed to contribute substantially to human and animal food intoxication and environmental and soil instability/degradation. Better sweet potato root quality was observed at optimum amount of nitrogen supply especially through organic sources. Furthermore, the more toxic nitrite is often associated with inorganic fertilizer application in the soil which usually associates in the human bodies with gastric cancer, to which infants are at a greater risk than adults, for several reasons. In this end, many researches have not being done in this case as to cube or reduce the health challenges associated with the consumption of agricultural toxic foods. The treatments were built into a randomized complete block design (RCBD), with 7 seven treatments replicated three times. The following treatments were used; poultry dropping, Neem leaf, Moringa leaf, Rice husk Dust, Rice Husk Ash, NKP fertilizer, and no soil amendment (control). The soil parameters studied include; soil pH, organic carbon, total nitrogen and cation exchange capacity, while the tuber nutrients analyzed for include; the ash, crude fat, vitamin C, moisture content, crude fibre, carbohydrate and crude protein. Results obtained showed significant differences among the treatments in all the parameters studied, except in tuber yield where all the treated plots yield same, but significantly increased the yield weight relative to the control. It was discovered that poultry dropping gave the greatest difference among other treatments in tuber yield. Generally, this study indicates that sweet potato production could be enhanced by the use of appropriate organic manure at suitable rate and at an appropriate time in the study area. It was also obtained that the soil pH and cation exchange capacity of the studied soils were highly improved mostly by the application of organic sources of the plant nutrients. The application of organic amendments significantly lowered the sweet potato tuber crude protein content, and increased the Vitamin C levels, thereby giving the organic sources of plant nutrients a credit as a safer way of producing food items that will give better human health safety.